2020
DOI: 10.33258/birci.v3i2.928
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Motivation on Employee Performance

Abstract: This research is motivated by the decline of employee performance over a period of time which results in the realization of the work not fully achieving the specified targets. The decline of employee performance is suspected by the decrease in the level of motivation possessed by the employee. The purpose of this study is to empirically prove that motivational factors have an influence on employee performance both descriptively and verifiatively. The research method used is descriptive method and survey method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
26
2
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(109 citation statements)
references
References 0 publications
8
26
2
7
Order By: Relevance
“…The analysis result of this study supports the fifth hypothesis with the finding work motivation has a positive and significant influence on employee performance. This finding underlines that work motivation is an important aspect in improving employee performance, which is also proven by some previous findings (Jeremy et al, 2019;Suharno et al, 2017;Hidayat et al, 2017;Kuswati, 2020;Riyadi & Rokhim, 2017;Sodiq, 2018). Suharto et al, (2018) found that there is a positive and significant influence of transformational leadership, work motivation, and work discipline on employee performance.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The analysis result of this study supports the fifth hypothesis with the finding work motivation has a positive and significant influence on employee performance. This finding underlines that work motivation is an important aspect in improving employee performance, which is also proven by some previous findings (Jeremy et al, 2019;Suharno et al, 2017;Hidayat et al, 2017;Kuswati, 2020;Riyadi & Rokhim, 2017;Sodiq, 2018). Suharto et al, (2018) found that there is a positive and significant influence of transformational leadership, work motivation, and work discipline on employee performance.…”
Section: Discussionsupporting
confidence: 85%
“…Motivation has a huge impact on better employee performance, considering that they are able to work optimally. This is in line with the study conducted by Suharno et al (2017); Hidayat et al (2017); Kuswati (2020); Riyadi & Rokhim (2017); and Sodiq (2018) who stated that work motivation can have a significant positive influence on employee performance. Therefore, the fifth hypothesis proposed in this study is: H5: Work motivation has a significant and positive influence on employee performance.…”
Section: Work Motivation and Employee Performancesupporting
confidence: 90%
See 1 more Smart Citation
“…Another factor that also affects employee performance is work motivation. Previous research has shown that work motivation affects employee performance (Dewi et al, 2019;Kuswati, 2020;Said et al, 2015). Motivation is a set of energy that comes from within and outside, which drives a person to achieve his goals (Colquitt et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Various empirical studies revealed mixed findings, which led to research gaps. Some researchers found that motivation positively affects employee performance (Guterresa et al, 2020;Kuswati, 2020), but other studies stated the opposite (Muchtar, 2016). Some researchers also denoted a positive effect of leadership on employee performance (Guterresa et al, 2020), but other studies could not prove the positive effect (Darojat et al, 2019).…”
Section: Introductionmentioning
confidence: 99%